2018
DOI: 10.1002/ecy.2481
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the vital rates of an Antarctic marine predator: the role of individual heterogeneity

Abstract: Variation in life‐history traits such as lifespan and lifetime reproductive output is thought to arise, in part, due to among‐individual differences in the underlying probabilities of survival and reproduction. However, the stochastic nature of demographic processes can also generate considerable variation in fitness‐related traits among otherwise‐identical individuals. An improved understanding of life‐history evolution and population dynamics therefore depends on evaluating the relative role of each of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 78 publications
7
60
0
Order By: Relevance
“…Female elephant seals recruiting at a young age are not a random subgroup of the population, but mostly those that experienced favorable conditions during early development (Oosthuizen et al, ). Our finding that individuals that recruit earlier in life survive and reproduce better than delayed breeders supports the hypothesis that recruitment age is an indicator or proxy of individual quality (Fay et al, ; Paterson et al, ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Female elephant seals recruiting at a young age are not a random subgroup of the population, but mostly those that experienced favorable conditions during early development (Oosthuizen et al, ). Our finding that individuals that recruit earlier in life survive and reproduce better than delayed breeders supports the hypothesis that recruitment age is an indicator or proxy of individual quality (Fay et al, ; Paterson et al, ).…”
Section: Resultssupporting
confidence: 86%
“…In theory, recruitment at an early age benefits individuals by shortening generation time and increasing the number of possible breeding opportunities over a lifetime (McGraw & Caswell, 1996). In support of this prediction, numerous empirical studies indicate a fitness gain among individuals that recruit at an early age (Fay, Barbraud, Delord, & Weimerskirch, 2016;Paterson, Rotella, Link, & Garrott, 2018;Zhang, Vedder, Becker, & Bouwhuis, 2015). However, the advantages of early breeding are often counter-balanced by elevated reproductive costs among younger first-time breeders (Desprez et al, 2014;Millon, Petty, & Lambin, 2010).…”
mentioning
confidence: 98%
“…Adult female bottlenose dolphins invest heavily over several years to raise their offspring (Arso Civil, Cheney, Quick, Thompson, & Hammond, ), like other mammal species such as elephants (Lee, ) and chimpanzees (Van Lawick‐Goodall, ). Providing such intensive parental care may have an impact on the female's subsequent reproduction (cost of reproduction, Paterson, Rotella, Link, & Garrott, ), as well as other demographic traits (trade‐offs) such as survival, which is the predominant trait for long‐lived species. In this study, we did not observe a trade‐off between current reproductive status and survival (see the “Adult survival” section).…”
Section: Discussionmentioning
confidence: 99%
“…We built models using the R package NIMBLE version 0.6‐10 (de Valpine et al, ) in R version 3.5 (R Core Team, ). As previous studies have suggested that age and year affect φ and p of Weddell seals (Cameron & Siniff, ; Stauffer, Rotella, & Garrott, ), and we had data from a large number of years for which at least some female vital rates have been shown to vary (Cameron & Siniff, ; Hadley et al, ; Paterson et al, ; Stauffer, Rotella, & Garrott, ), we structured our a priori candidate models for males such that temporal variation was allowed for both φ (σfalse^yrφ) and p (σfalse^yrp) by including random effects of year for each parameter that were normally distributed with a mean of zero. To evaluate support in the data for alternative predictions of how φ might change with age, we used five different model structures for the log‐odds of φ .…”
Section: Methodsmentioning
confidence: 99%
“…Survival rates of female Weddell seals are moderate for pups and yearlings and quite high for older animals; adult females endure costs to survival from pup production and rearing (Chambert et al, ; Chambert, Rotella, & Garrott, ; Hadley, Rotella, & Garrott, ; Paterson, Rotella, Link, & Garrott, ). Additionally, actuarial senescence that commences immediately after age at first reproduction, which typically occurs at 8 years of age, was recently detected in female Weddell seals (Paterson et al, ). Unique reproductive costs might cause differences in age‐specific survival rates and senescence patterns between male and female Weddell seals.…”
Section: Introductionmentioning
confidence: 99%